Hubungan Tingkat Literasi Kesehatan Mental Pada Masyarakat Dengan Perilaku Dalam Mencari Bantuan - Tarikah Amaliah; Fathra Annis Nauli; Riri Novayelinda (Peneliti.net, 2022)
The level of mental health literacy of individual is often associated with help seeking behavior. This study aims to find the relationship between mental health literacy level in the community and help seeking behavior. Methods: The design of this study is descriptive correlation with a cross sectional approach. The sample of this study are 100 people in the working area of the Rawat Inap Sidomulyo Health Center Pekanbaru in accordance with the inclusion and exclusion criteria that had been determined by using a sampling technique stratified random sampling. The measuring instrument used are mental health literacy scale questionnaire and mental health assistance seeking scale questionnaire that have been tested for validity and reliability. Statistical test analysis used univariate statistical test and bivariate statistical test using chi-square test. The results of the validity test for the mental health literacy level questionnaire were 17 valid statements with reliability results obtained by the cronbach alpha value of 0.862 and the validity test for the help seeking behavior questionnaire obtained cronbach alpha 0.884. The results of the study based on univariate statistical tests showed that the majority of people were in the age range of 17-25 years or late teens (45%) female (62%) high school education (44%) working as college students or students (35%) with mental health literacy levels high majority (61%) and low help seeking behavior (56%). The results of the bivariate statistical test between mental health literacy level in the community and help seeking behavior obtained P value (0.000) < (0.05). There is a relationship between mental health literacy level in the community and help seeking behavior.